Designing of an academic supporting program to increase the english language knowledge in the students of second year of basic education at “Luis Fernando Vivero” elementary school during the period 2010 - 2011. - Chanatasig Montaluisa, Blanca Magaly (2012)
This research work was done at ―Luis Fernando Vivero‖ Elementary School with the main purpose to increase the English Language knowledge in which the researchers used research methods able to pick up true information to know the students’ weaknesses in the English Language teaching learning process.The principal objective in this thesis is the designing of an academic supporting program to increase the English language knowledge in the students of second year of basic education at ―Luis Fernando Vivero‖ elementary school. The survey was applied to students and teachers in the second year of basic education within the institution, so each group helped to identify the problem through a good information about their experiences in the English language teaching, the obtained results through the surveys showed the importance of designing an academic supporting program with easy activities to learn English language focused on the skills to increase the student’s academic level improving the standars in the English language teaching. For this reason the proposal was designed taking into account the polled people’ needs about the subject. This program is a tool designed to benefit students who need to learn the English Language in a funny way.